PENDAMPINGAN PENGAJARAN TAHSIN AL-QUR’AN DI PONDOK PESANTREN QORYATUL QUR’AN KABUPATEN SUKOHARJO - Murdianto; Wahid Fairuzziyad Rofif; Nurika Nuralifah (LPPM STAIMAS WONOGIRI, 2024)
Islamic boarding school as a place to gain knowledge is a very effective educational institution in order to realise the goals of Islamic education. The importance of a santri being able to read the Qur'an properly and correctly, in order to improve their quality as a santri, so we together with the management of the Qoryatul Qur'an Islamic Boarding School, Sukoharjo, Central Java observed the actual extent of the number of santri who were not fluent in reading the Qur'an in accordance with the rules of Tahsin and Tajweed. The results can be concluded that there are still some students of Qoryatul Qur'an Islamic Boarding School, Sukoharjo, Central Java who do not understand well the rules of tahsin and tajweed in reading the Qur'an. Tahsin teaching assistance in order to improve the ability to read the Qur'an still needs to be more emphasised (focus) to the students. They are very enthusiastic to be able to participate in this programme, besides that because they are also required to be responsible (musyrif and musyrifah) for the next generation (graduates / graduating class). Tahsin teaching assistance that will be held periodically (sustainable) in the next stage, especially for students who still want to continue or improve and smooth their memorisation of the Qur'an, as well as to add experience and knowledge related to Tahsin Al-Qur'an, so that the hope can be a motivation or encouragement for other students, so as not to stop learning Tahsin Al-Qur'an.